The Effect of Learning Everyone is a Teacher Here in Combined Differentiate Learning on Science Literation Ability and Learning Motivation - Muhammad Nur; Reski Aggun Sasmita; Andi Badli Rompeggading; Rizal Irfandi (Postgraduate, University of Mataram, 2023)
This study aims to determine the effect of the learning strategy Everyone is A Teacher Here combined with a differentiated learning strategy on scientific literacy skills and learning motivation on environmental pollution material. This research method is a quasi-experimental design with a pretest-posttest control group design. The sampling technique is by means of cluster random sampling. The instruments used in this study were descriptive tests and motivation questionnaires. Results Based on the data analysis of scientific literacy ability, the posttest average in the experimental class was 74.2 while in the control class it was 60.89 with the results of hypothesis testing (t-test) obtained tcount (3.59) > ttable (1.68) indicates that H0 is rejected and H1 is accepted. Furthermore, based on the results of the motivational data analysis, the average percentage in the experimental class was 85.01% while in the control class it was 74.98%, with the results of hypothesis testing (t-test) obtained tcount (9.20) > ttable (1.68) indicates that H0 is rejected and H1 is accepted. The results of this study indicate that there is an influence of the learning strategy Everyone is a Teacher Here combined with a differentiated learning strategy on scientific literacy skills and learning motivation for environmental materials for class X MIPA UPT SMA Negeri 1 Wajo.